1988
DOI: 10.1007/bf00139811
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variations of surface air temperature at major industrial cities of India

Abstract: Local temperature is one of the major climatic elements to record the changes in the atmospheric environment brought about by industrialization and urbanization, Long-term variations of seasonal and annual surface air temperature at six major industrial cities of India (Calcutta, Bombay, Madras, Bangalore, Pune and Delhi) have been studied, using data for the past 86 to 112 yr. Comparative analysis of the temperature data of six nonindustrial stations has also been done. The long-term change in the temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 17 publications
2
35
1
Order By: Relevance
“…The summer season also shows significant cooling trend due to slightly decrease in Tmax. This cooling trend in Junagadh (Saurashtra Region) Gujarat, India temperature is supported by studies conducted by other researchers (Rupa Kumar and Hingane, 1988). These authors studied the temperature for Junagadh (Saurashtra region) Gujarat, India during the period 1980-2007 and observed a cooling trend, but not significant at any level.…”
supporting
confidence: 61%
“…The summer season also shows significant cooling trend due to slightly decrease in Tmax. This cooling trend in Junagadh (Saurashtra Region) Gujarat, India temperature is supported by studies conducted by other researchers (Rupa Kumar and Hingane, 1988). These authors studied the temperature for Junagadh (Saurashtra region) Gujarat, India during the period 1980-2007 and observed a cooling trend, but not significant at any level.…”
supporting
confidence: 61%
“…A 9-point Gaussian lowpass filter was used to give a smoothed curve a s was used earlier in Indian studies by Hingane e t al. (1985) and Rupakumar & Hingane (1988). The smoothed curve is drawn as the time series in addition to the trend line.…”
Section: Data and Analysismentioning
confidence: 99%
“…Their analysis showed that the mean annual temperature in India has increased by 0.4 "C during the past century. Rupakumar & Hingane (1988) have reported the results of the analysis of long-term trends of surface air temperatures of 6 industrial cities in India. They concluded that 3 cities (Calcutta, Bombay and Bangalore) showed a significant warming trend, 2 cities (Madras a n d Pune) did not show any significant trend a n d 1 city (Delhi) showed a significant cooling trend (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the stations are given in Table 1. The classification of cities is similar to that of Ren et al [18] and Rupa Kumar et al [12]. Stations with altitude more than 1000 m are considered as hill stations (https://en.wikipedia.org./wiki/Hill_station).…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…While, all the major cities along the coasts show a significant increasing trend in almost all the seasons for the periods 1971-2013 and 1901-2013 (Figure 2 and relevant explanation are given in section 4). The marked differences in the temperature trends at the stations are determined more by the location of the stations with respect to the broad areas of increasing/decreasing trends observed over India rather than the stations being highly industrialized/non-industrialized [12].…”
Section: Major Citiesmentioning
confidence: 95%